2009
DOI: 10.1016/j.gde.2009.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics of tooth development

Abstract: Organogenesis depends upon a well-ordered series of inductive events involving coordination of molecular pathways that regulate the generation and patterning of specific cell types. Key questions in organogenesis involve the identification of the molecular mechanisms by which proteins interact to organize distinct pattern formation and cell fate determination. Tooth development is an excellent context for investigating this complex problem because of the wealth of information emerging from studies of model org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
160
0
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(166 citation statements)
references
References 43 publications
0
160
0
6
Order By: Relevance
“…Key signaling pathways including Bmp, Fgf, Notch, and Eda are impaired in the absence of p63 (Laurikkala et al 2006). The importance of the signaling that takes place at the placode stage is further highlighted by the phenotype of several mouse mutants where tooth development stops before epithelial budding (Bei 2009b).…”
Section: Signal Network and Signaling Centersmentioning
confidence: 99%
See 1 more Smart Citation
“…Key signaling pathways including Bmp, Fgf, Notch, and Eda are impaired in the absence of p63 (Laurikkala et al 2006). The importance of the signaling that takes place at the placode stage is further highlighted by the phenotype of several mouse mutants where tooth development stops before epithelial budding (Bei 2009b).…”
Section: Signal Network and Signaling Centersmentioning
confidence: 99%
“…The deletion of the function of several of these either alone or together with another transcription factor in the same family results in tooth arrest at placode or bud stage. All four signal pathways have been shown to be involved in the regulation of these transcription factors (Bei 2009b). For example, Bmp4 induces the expression of Msx1 and Fgf8 induces the expression of Pax9 (Vainio et al 1993, Neubüser et al 1997).…”
Section: Signaling Network Regulating Tooth Developmentmentioning
confidence: 99%
“…These signaling pathways are part of a larger odontogenic signaling network involving genes that are absolutely necessary for tooth formation in man and mouse, such as the MSX1 transcription factor. 23,24,[66][67][68]69,70,71 …”
Section: Disclosure Of Potential Conflicts Of Interestmentioning
confidence: 99%
“…2,[5][6][7] Studies of animal development have identified many genes participating in dental morphogenesis. [8][9][10][11] Additionally, studies on human genetic disorders have identified dysfunctional mutations on coding region of some genes that result in tooth malformation. 12,13 However, very few examples of genetic polymorphisms associated with common dental variations have been identified.…”
Section: Introductionmentioning
confidence: 99%